Finance Technology as a Solution to Get Capital for Small Business Today: Teknologi Finance Sebagai Solusi Mendapatkan Modal Bagi Usaha Kecil Saat Ini - Sutikno, Sutikno; Kuruppuarachchi, Duminda (Jurnal Keuangan dan Perbankan (KEBAN), 2021)
Financial technology in Indonesia has enormous potential and is easy to manage compared to banks. Financial technology is also easier to use as a source of capital for both stable companies and start-ups. Despite the fact that the great potential can be felt by the public. Other current financial technology companies can integrate funding, financing, and profit distribution systems. In the current era, it is supported by the use of digitalization process technology and using the Financial Technology (FinTech) system so that it is economical and efficient. The benefits of this research are expected to be a solution to capital problems that have been faced by small businesses. In addition, it also encourages the growth and development of entrepreneurship for young people, which can be started by establishing a startup company. This research approach is descriptive qualitative. The data taken is primary data with focus group discussions and interviews as data collection techniques. The research object consists of 30 startups owned by youth in Jakarta. The results of this study can be used as an alternative economical solution to capital problems for small businesses and startup companies. The Financial Technology System is a system that is able to integrate funding, financing, investors, startup companies, Financing Guarantee Institutions, and Banks